EARNING PERSISTENCE ON FIRM TAX DIFFERENCES AND FAMILY OWNERSHIP - Kusumawati, Synthia Madya; P, Hyashinta Dyah (Universitas Multimedia Nusantara, 2020)
Abstract- Prior research find evidence consistent with the hypothesis that future earnings influenced by difference between accounting and fiscal earnings (book tax differences). Many investors forming expectations of future earnings information derived from the difference between fiscal and commercial earnings, there were some investors would satisfied to see small differences between fiscal and commercial earnings, otherwise have the opposite view. This study aim to investigate how book-tax difference and family ownership play a role in the persistence of earnings. The authors using a sample 692 firm years of Indonesian listed companies within 2011-2016, they estimate cross-sectional regressions of the proxy for book-tax differences and family ownership on earning persistence. The study found that current pre-tax earnings can predict future earnings and also firm years with large book-tax difference have less earnings persistence than firm years with small book tax difference. Further, this study found no evidence that family ownership have significant role in persistence of earnings. Keywords: Earning Persistence, Future earnings, Pre-tax earnings, Book tax difference, Family Ownership.